ANALISIS CAPAIAN PEMBELAJARAN KURIKULUM MERDEKA DALAM MENGEMBANGKAN MATERI PEMBELAJARAN PAI BUDI PEKERTI BERBASIS NILAI-NILAI PENDIDIKAN MULTIKULTURAL - Ulfatul Chasanah; Ahmad Marzuki; Askhabul Kirom (Journal Multicultural of Islamic Education, 2024)
In the independent curriculum, learning outcomes (CP) are the minimum competencies that students must achieve for each subject, including PAI and Character. As an integral part of the national education system, PAI aims to teach Islamic religious values, strengthen religious identity, and help students develop attitudes and behavior that are in accordance with Islamic teachings. PAI taught in the context of the Independent Curriculum not only functions as religious learning, but also as a vehicle for developing multicultural awareness and fostering attitudes of tolerance and cooperation between students from various backgrounds. The research approach used by researchers in this study is a qualitative approach with the type of literature research (library research). The data collection stages carried out in this research only used documentation techniques. Researchers used analysis in this research with content analysis. From the results of the research conducted, it can be concluded: 1) The content of multicultural education values ​​in the Learning Achievements of the PAI Budi Pekerti subjects in the independent curriculum, namely tolerance, moderation, humanity, mutual respect and peace. These values ​​are spread in the learning outcomes of Phases E and F in elements of the Koran and Hadith, Fiqh, Aqidah, Morals, and the History of Islamic Culture.